The Use of Educational Games to Improve Understanding of Islamic Religious Education Materials at MI Roudlotul Khuffadz Sorong - Nur Janah; Budi Santoso; Firman Firman (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to analyze the effect of using educational game media in improving the understanding of Islamic Religious Education material in MI Roudlotul Khuffadz Sorong students. The study used a quantitative approach with a quasi-experimental design of the nonequivalent control group design. The research sample consisted of 20 students divided into an experimental group and a control group. Data collection techniques used tests, observation, and documentation. The research instrument has met the validity test with 22 valid questions and high reliability with a Cronbach Alpha value of 0.87. Data analysis was carried out through normality tests, homogeneity tests, t-tests, and N-Gain calculations. The results showed that the average posttest of the experimental group was 82.6, higher than the control group at 68.3. The N-Gain value of the experimental group was 0.68 in the medium category, while the control group was 0.29 in the low category. The t-test results showed a significance value of 0.003 <0.05, which means there is a significant effect of the use of educational game media on student understanding. In addition to improving learning outcomes, educational game media also increases student learning activities in the good to very good category. Thus, educational game media is effectively used in Islamic Religious Education learning in elementary schools.